PENGARUH MODEL PEMBELAJARAN GEO-STAR TERHADAP KEMAMPUAN BERPIKIR SPASIAL SISWA PADA MATERI PETA DI KELAS X SMA NEGERI 1 IX KOTO SUNGAI LASI - Oktafiani, Nidia; Suasti, Yurni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the Geo-STAR learning model on students' spatial thinking at SMA Negeri 1 IX Koto Sungai Lasi. The research method used in this study was the Quasi-Experimental Method with a Nonequivalent Control Group Design. The sample in this study consisted of students in class X.E3 as the experimental class, which was given treatment using the Geo-STAR model. Spatial thinking data were collected through tests and analyzed using the T-test. The results of the study showed that there was an effect of the Geo-STAR learning model on the spatial thinking of students in class X.E3, with the experimental class's posttest average of 85 being higher than the control class's average of 76. The results of the T-test showed a significance level (Sig.) of 0.000; since the significance value is smaller than 0.05 (0.000 < 0.05), Ho is rejected and Ha is accepted.Keywords: Geo-STAR Learning Model, Map, Spatial Thinking.